Network of social preferences of humpback whales (≥ 5 encounters; n edges = 1,527; n whales = 136) based upon the Generalized Affiliation Index (only positive indices are displayed) and color-coded by aspects of habitat use and behaviour that were found to yield significant Assortativity Coefficients (ACs), which indicate correlation between these traits and social organization. - Janie Wray (457395); Eric Keen (11014169); Éadin N. O’Mahony (11014172) (2021)
P-values of positive ACs (affiliations) and negative ACs (avoidances) are provided below each network (see text for interpretation of significance). In all networks the placement of individuals remains the same, demonstrating related patterns in the distribution of individual traits. Vertex size reflects the number of observations of each individual. Thicker, darker edges represent statistically significant associations based upon data stream permutations (1,000 iterations). Networks built with igraph in R using the Fruchterman-Reingold layout.